Microplastic distribution in the Atlantic and Arctic Ocean through continuous underway sampling - Isabel Goßmann; Laura Simon-Sánchez; Jens Meyerjürgens; Claudia Lorenz; Ashani Arulananthan; Fangzhu Wu; Sebastian Primpke; Gunnar Gerdts; Jes Vollertsen; Alvise Vianello (PANGAEA, 2025)
The COntinuous MicroPlastic Automatic Sampling System (COMPASS) was utilized for sampling of microplastic (MP) samples. Developed by Aalborg University in Denmark, COMPASS is a fully enclosed, stainless-steel, plastic-free system designed for continuous, automatic MP sampling (>10 μm). It can operate unsupervised for up to 9 hours, filtering 500 to 1,500 liters of water per hour through stainless-steel filters with mesh sizes of 300 μm and 10 μm (filter diameter: 167 mm). This method provides horizontal distribution data and resolution for MPs. Depending on the length of each transect, a specific number of subsamples were collected. Sub-surface water samples were continuously sampled during steaming at a depth of 4 meters along five transects, covering 1,600 nautical miles from the Norwegian coast to Bear Island in the Arctic Ocean. MP were analyzed using Fourier-transform infrared imaging micro-spectroscopy, revealing concentrations ranging from 7 to 491 items per cubic meter.